Red hot Fury : a shades of Fury novel - Mackenzie, Kasey (New York : Ace Books, 2010)
"It's far from business as usual when the body of a sister Fury washes up in Boston Harbor. But when Riss reports that the corpse's identity has been magically altered, she's immediately--and inexplicably--suspended from her job. Then a human assassin makes an attempt on her life, and Riss realizes that someone is trying to stir up strife between mortals and arcanes. When a Fury gets mad, she gets even, and Riss is determined to uncover the truth. Without the support of the mortal PD, she turns to the one man she can trust to watch her back: shape-shifting Warhound Scott Murphy. But since Scott is also Riss's ex, she'll have to keep a short lease on more than just the supernatural rage that feeds her power as they try to solve a murder--and stop a war..."--P. [4] of cover.
Keywords: Furies (Roman mythology) -- Fiction; Murder -- Investigation -- Fiction; Shapeshifting -- Fiction; Man-woman relationships -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction; Fantasy fiction